Unusual Presentation with Orbital Mass in a Child with Precursor B-Cell Acute Lymphoblastic Leukemia - Lalita Sathitsamitphong; Rungrote Natesirinilkul; Worawut Choeyprasert; Pimlak Charoenkwan (Case Reports in Hematology)
Orbital involvement is one of the extramedullary manifestations in acute leukemia. It is common in acute myeloid leukemia, but rare in acute lymphoblastic leukemia (ALL). We described a 3-year-old girl who presented with progressive proptosis of the right eye and was later diagnosed with precursor B-cell ALL. Initial blood count showed Hb 6.9 g/dL, WBC 42,000/mm3, lymphoblast 50%, and platelet count 185,000/mm3. Bone marrow aspiration revealed 90% lymphoblasts with positivity for CD10, CD19, CD20, CD22, and HLA-DR markers. Computed tomography (CT) scan of the brain and orbit revealed a homogeneous enhancing mass involving the right orbit with intracranial extension. The cytogenetic study showed 46,XX chromosomes. After 4 weeks of induction chemotherapy for very high-risk ALL, although the bone marrow was in remission, the proptosis was partially resolved. CT scan confirmed a decrease in size of the right orbital mass and degree of intracranial extension. Unfortunately, the patient abandoned the treatment after the induction chemotherapy. The actual incidence of orbital involvement in ALL is unknown. Previous case reports describe diverse manifestations of orbital involvement in ALL. The involvement may be unilateral or bilateral, may occur at first diagnosis or at relapse, and may be seen in isolation or with other systemic symptoms. There is no standard treatment protocol. Chemotherapy with or without radiotherapy is generally suggested. The role of upfront hematopoietic stem cell transplantation remains inconclusive. The previously reported prognosis of ALL with orbital involvement is poor.